Dosimetric comparison of five different techniques for craniospinal irradiation across 15 European centers: analysis on behalf of the SIOP-E-BTG (radiotherapy working group). (2nd September 2018) - Seravalli, Enrica; Bosman, Mirjam; Lassen-Ramshad, Yasmin; Vestergaard, Anne; Oldenburger, Foppe; Visser, Jorrit; Koutsouveli, Efi; Paraskevopoulou, Chryssa; Horan, Gail; Ajithkumar, Thankamma; Timmermann, Beate; Fuentes, Carolina-Sofia; et al.
Abstract: Purpose: Conventional techniques (3D-CRT) for craniospinal irradiation (CSI) are still widely used. Modern techniques (IMRT, VMAT, TomoTherapy ®, proton pencil beam scanning [PBS]) are applied in a limited number of centers. For a 14-year-old patient, we aimed to compare dose distributions of five CSI techniques applied across Europe and generated according to the participating institute protocols, therefore representing daily practice. Material and methods: A multicenter ( n = 15) dosimetric analysis of five different techniques for CSI (3D-CRT, IMRT, VMAT, TomoTherapy ®, PBS; 3 centers per technique) was performed using the same patient data, set of delineations and dose prescription (36.0/1.8 Gy). Different treatment plans were optimized based on the same planning target volume margin. All participating institutes returned their best treatment plan applicable in clinic. Results: The modern radiotherapy techniques investigated resulted in superior conformity/homogeneity-indices (CI/HI), particularly in the spinal part of the target (CI: 3D-CRT:0.3 vs. modern:0.6; HI: 3D-CRT:0.2 vs. modern:0.1), and demonstrated a decreased dose to the thyroid, heart, esophagus and pancreas. Dose reductions of >10.0 Gy were observed with PBS compared to modern photon techniques for parotid glands, thyroid and pancreas. Following this technique, a wide range in dosimetry among centers using the same technique was observed (e.g., thyroid mean dose: VMAT: 5.6–24.6 Gy; PBS: 0.3–10.1 Gy). Conclusions: The investigated modern radiotherapy techniques demonstrate superior dosimetric results compared to 3D-CRT. The lowest mean dose for organs at risk is obtained with proton therapy. However, for a large number of organs ranges in mean doses were wide and overlapping between techniques making it difficult to recommend one radiotherapy technique over another.